The Global Advertising of a Local Brand in Terms of Analyzing the Visual Content: Turkish Airlines Globally Yours Advertising Campaign - Küçükerdoğan, Rengin; Zeybek, Işıl; Ekin, Volkan (The Turkish Online Journal of Design, Art and Communication, 2011)
Globalization is a process where economic, political, social and cultural values and the build up of these values are spread beyond the national borders to the world. This way, differing social cultures and beliefs gain recognition and the relationships between countries become ubiquitous. (Mc Chesney&Wood&Foster 1999:7). During this globalization process, advertising brings together a product or a service with a cultural symbol and presents it to audiences. According to this definition then, airline transport, which is a modern, fast, and prestigious mode of transport, has been largely affected by globalization. As a result, the intensifying competitive environment has led airline companies to shift from a more local market to a more global one. Advertising is often used to create brand recognition and value and, along with this, sports marketing practices, which is a new terminology, when the cultural symbols they use meet with target audiences, a platform of communication is created. In this study, by taking sports marketing as a starting point, the communication strategies of Turkish Airlines, which has taken great steps in terms of brand recognition, and the visual and linguistic messages of their advertising campaign “Globally Yours” will be analyzed.
Keywords: Cultural symbols; global advertisement; brand communication; sports marketing; Turkish Airlines; kültürel semboller; global reklam; marka iletişimi; spor pazarlama; Türk Hava Yolları